Model Trauma-Informed Islamic Counseling (TIIC) Untuk Pemulihan Trauma Bencana Banjir di Komunitas Muslim - Muhammad Saffuan Abdullah (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
Flood disasters represent one of the most recurrent natural hazards in Southeast Asia and the Muslim world, often resulting in long-term psychological consequences such as post-traumatic stress disorder (PTSD), chronic anxiety, and social dysfunction. Although Trauma-Informed Care (TIC) has been widely applied in post-disaster interventions, existing models are largely grounded in Western epistemologies that may not fully align with the religious and cultural frameworks of Muslim communities. This article aims to develop the Trauma-Informed Islamic Counseling (TIIC) Model as a contemporary Islamic counseling framework for flood-related trauma recovery. Using a conceptual model development design grounded in the istiqrā’ (inductive) approach, this study synthesizes Islamic textual sources, classical Islamic psychological thought, and recent empirical findings (2021–2025) in trauma and Muslim mental health research. The TIIC model integrates core principles of Trauma-Informed Care with Islamic epistemology, including tawḥīd, maqāṣid al-sharī‘ah, and the concept of ummah, through a six-stage, phased intervention addressing psychological, spiritual, and social dimensions of trauma recovery. This article contributes to the advancement of trauma-informed Islamic counseling by offering a culturally responsive and theoretically grounded model relevant to recurrent climate-related disasters in Muslim societies.